A study of noise transmission through cylindrical shell using modal truncation approach - El-Hafidi, Ali; Martin , Bruno; Faris, Waleed Fekry; Lay, Béatrice (Inderscience Publishers, 2011)
The study of the vibroacoustic behavior of cylindrical structure like aircraft fuselage requires the establishment of very large models, and the numerical results which can be obtained are often difficult to interpret. On the other hand, the study of simple structures such as cylindrical shells is useful to validate the criteria and tools that can be used to simplify the models of complex structures. The presented study concerns the sound transmission through a cylindrical shell coupled to a cavity and subjected to an incident acoustic wave. Noise reduction is obtained and validated by a numerical method which uses structural and acoustical modes. A criterion for selecting eigen modes for the modal truncation is presented. Based on a principle of modal coupling, this criterion allows a judicious choice of modes that have an important influence on noise reduction. This criterion is used to reduce the length of acoustical and mechanical bases and to decrease time calculation.